PENGARUH PENGGUNAAN CEBEX 112 TERHADAP SIFAT-SIFAT TEKNIS MORTAR SEMEN DENGAN AGREGAT HALUS BUBUK LIMBAH BATA MERAH - Widodo, Haryadi; Satyarno, Iman; Kardiyono T., Kardiyono T. (Civil Engineering Forum Teknik Sipil, 2009)
Earthquake in Jogjakarta on 27 May 2006 has caused severe damage to two hundred thousand buildings. Such damage produced a lot of rubbles and, on the other hand, also the need of a huge amount of material to rebuild the buildings. Currently, rubbles, including brick rubbles, are treated only as rubbish and polluting the environment. Anticipation efforts to such problem are required. One of the solution alternatives is a recycling procedure for brick rubbles. Because high water absorption is required, recycling brick rubble is unique that it requires high water cement ratio for mixing the brick masonry wall rubbles. This research attempted to identify the influence of Cebex 112, a mortar plasticizer additive, to cement mortar with brick powder. The mortar workability consistency was measured using the flowtable, ranged from 70% to 90%, showing the easiness of the mortar workability, but without too much bleeding when molded. Sample was made in cube shape of 50mm x 50mm x 50mm. Four ratios of portland cement (pc) to fine aggregate (fa) were used, which were 1pc:4fa, 1pc:6fa, 1pc:8fa and 1pc:10fa. Five ratios of Cebex 112 additive were 0.0%, 0.2%, 0.4%, 0.6% and 0.8% of the Portland cement weight. The samples made were 200 cubes and compression test, absorption test and specific gravity test were given. Results showed that Cebex 112 improved workability and volume due to the reaction between cement and Cebex 112. Admixture is air entrained controlling the microscopic air bubbles which increased the cohesion and provides lubrication for fine aggregate. Cebex 112 decreased the compacting value, improved the absorption and decreased the mortar specific gravity. It also may reduce the cement consumption. This admixture reduced required water at cement ratio 1pc:4fa, but increased at 1pc:6fa, 1pc:8fa and 1pc:10fa. The maximum compaction value was at 1pc:4fa with Cebex 112 content of 0.00% and 17.24 MPa. The minimum was at 1pc:10fa, with Cebex 112 content of 0,6% and 2.67 MPa. The mortar highest specific gravity portion was 1pc:4 fa, 0.0% with 1,71 MPa and the lowest was at 1pc:4fa, with Cebex 112 content of 0.8% and 1.32 MPa. The 24 hours highest absorption was at 1pc:8fa, 0.6% with Cebex 112 content of 29.3% and the lowest was at 1pc:4fa, with Cebex 112 content of 0.0% and 22.3%. These figures show that mortar cement with recycled brick can be used for wall partition and wall interior.